THE DEVELOPMENT OF A KNOWLEDGE – BASED DIGITAL INNOVATION ECONOMY AS A SOURCE OF ACCELERATION OF COMMUNITY DEVELOPMENT (E Conference Zone, 2022)
It is necessary to increase the potential of the younger generation, to develop its ideological and ideological thinking, to arm oneself with the methods and means of seeking new innovative ideas, so that any idea can demonstrate advanced techniques, technology and new inventions